The dynamics of political buzzer domination on TikTok and the mechanism of young voter opinion formation in Surabaya during the 2024 Presidential Election: Dinamika dominasi buzzer politik di TikTok dan mekanisme pembentukan opini pemilih muda di Surabaya pada Pilpres 2024 - Nayla Zhei Aurel Meilan; Lingga Kencana; Miftakhul Khoir (Jurnal Politik Indonesia (Indonesian Journal of Politics), 2026)
This study examines how the dominance of political buzzer accounts on TikTok shaped the political opinions of young voters in Surabaya during the 2024 Indonesian Presidential Election. To address this question simultaneously from two angles (quantitative measurement and qualitative explanation), the study adopts a mixed-methods design with an explanatory sequential structure: quantitative data first, qualitative data to unpack the mechanisms that numbers alone cannot reveal. Survey data were collected retrospectively from 113 young voters (April-May 2026), and in-depth interviews were conducted with 10 informants (May 2026), asking participants to recall their TikTok consumption experiences and opinion formation processes during the 2024 campaign period. A simple linear regression test yielded an R² value of 0.541 (p < 0.001), indicating that buzzer domination accounts for 54.10% of the variation in voter opinions. Inductive thematic analysis then identified four mechanisms through which this influence operates: message repetition as normalization, the construction of artificial credibility, emotional content as a catalyst for uncritical acceptance, and content virality as an illusion of majority consensus. Unlike most comparable studies that focus on Twitter/X at the national level, this study examines TikTok dynamics specifically at the city level and uncovers psychological layers that statistical analysis alone cannot detect. The findings underscore the need for stricter regulation of digital political campaigns, alongside a more serious commitment to digital literacy education for younger generations.